MISKONSEPSI SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) BERDASARKAN PROSES BERPIKIR KRITIS DITINJAU DARI KEMAMPUAN AWAL - Rani Pratiwi (Eksponen, 2018)
This research aims to determine the misconceptions of students of SMPN 1 Negeri Besar with high initial ability, moderate and low in solving the problem SPLDV based on critical thinking process. The research was a qualitative research. The subjects of the research were taken by using purposive sampling. The method used is test method and interview method equipped with CRI (Certainty of Response Index). The result of the research is that students with high initial ability do not experience misconception at every stage of critical thinking process, students with initial ability is experiencing misconception at analytical stage that is the concept of negative integer operation on both sides, whereas students with low initial ability have misconception at analysis stage and alternative settlement stage.